Digital Transformation in Human Resource Management: Challenges and Opportunities for Modern Organizations - Idel Eprianto; Djunaedi; Takim Mulyanto; Sumarno Sumarno (PT. Anagata Sembagi Education, 2025)
Digital transformation in human resource management has become a major factor in improving the efficiency and effectiveness of HR management in the modern era. Along with the rapid development of technology, many organizations have begun to turn to digital systems to handle various HR functions, such as recruitment, training, payroll, and performance management. This research aims to analyze the impact of digital transformation in HR management, focusing on the challenges faced by organizations and the opportunities that can be utilized to improve HR management. The method used is a literature study and qualitative analysis of various secondary sources, including scientific articles and industry reports. The results show that the application of digital technology in HR provides significant benefits, such as increased operational efficiency, reduced administrative costs, and more accurate and measurable data-based performance management. Technologies such as cloud-based systems, artificial intelligence (AI) for recruitment, and analytics platforms provide opportunities for organizations to make faster, evidence-based decisions However, digital transformation also presents challenges, including resistance to changes in organizational culture, data security and privacy concerns, and digital skills gaps among employees. The implications of this research suggest that organizations must provide adequate technology training, overcome cultural barriers and ensure personal data protection in order to harness the full potential of digital transformation. Organizations that successfully manage these challenges will gain a competitive advantage, create a more efficient work environment and improve the overall employee experience.